Health status of banana in the national and regional germplasm collections - Dela Cueva, Fe M. (Transactions of the National Academy of Science and Technology, 2011)
A large collection of wild, edible, and introduced banana cultivars is being maintained in the national and regional germplasm collections at the Institute of Plant Breeding, UPLB and Bureau of Plant Industry, Bago-Oshiro, Davao City. Banana bunchy top virus (BBTV, Banana bract mosaic virus (BBrMV), and Cucumber mosaic virus (CMV) are the major viruses detected in the germplasm collections. Virus-infected accessions and/or cultivars were replaced with virus-free materials. Efforts to eliminate viruses through in-vitro techniques are also being exerted. In BPI Davao, 10 out of 85 accessions were infected either by BBTV or BBrMV, hence, they were eradicated from the collection. In IPB, BBrMV and CMV were detected from wild Musa balbasiana collections. A total of 268 samples from 61 banana cultivars and accessions in in-vitro culture were indexed through ELISA. All samples were found to be negative to viruses except one sample from Grand Naine which was BBTV-positive. In the repository glasshouse, an ex-situ gene banking strategy, a total of 64 local and introduced banana cultivars were indexed against BBTV, BBrMV, and CMV. Of these, 32 accessions were newly recollected to replace the accessions that were lost either by natural calamities or disease infection. Moradong Puti, was BBTV-positive while one Pondol plant and two Moko plants were CMV-positive. Infected plans were eradicated from the collections.